Value creation of well-being data : opportunities for a national personal health record - Koivisto, Niko (2020)
The aim of this master’s thesis is to examine the value creation potential of wellbeing data in a national personal health record. The amount of well-being data is growing exponentially as a product from the increased popularity of wearable devices. A large amount of the gathered data goes currently unused. For well-being data to be of use, it needs to be stored in large quantities. Well-being data can be stored in personal health records, through which the data can be viewed and managed. The Finnish Social Insurance Institution is developing a national personal health record where Finnish citizens will be able to upload their well-being data. The well-being data will be gathered by commercial solutions and will be able to be used by different healthcare specialists in the future. This project provides a lucrative opportunity to study the value creation of well-being data in a national personal health record. This research will provide insights into what is needed for well-being data to create value through a national personal health record. The research was conducted by first conducting a literature review on relevant literature. After this, an empirical qualitative research was conducted with data gathered through semi-structured interviews. The interviews were conducted on professionals with backgrounds in relevant fields to a personal health record, well-being data, health technology and healthcare. According to the study value can be created with well-being data through a national personal health record by providing enhancement to different entities through an easily accessible platform for different users. This allows value co-creation by these users and provides the basis for the public and private sector actors to work in balance, by allowing financial constructs to support the needed commercial actors.